NATIONAL SECURITY POLICY IN SWITZERLAND (Annual of the Faculty of Philosophy in Skopje, 2019)
The national security policy of Switzerland is based upon the specifics of theSwiss country and it is distinguished with great complicacy and complexity. Hence,the examination of the security policy should be founded of its complete comprehensionand thorough perception of the conditions in order to avoid improvisation andpartiality. This signifies that the security policy should be rationally founded and tosynthetize the efforts of all of the security actors in order to provide the necessary levelof security, for the society, the nation, and for the citizens. Generally, the alterednature of security threats conditioned the need for redefining the security policy ofSwitzerland and also imposed for adoption of new approaches toward security. Acceptingsuch reality, Switzerland has to adjust to the new circumstances for the protectionof the national interests and the neutrality policy. The Adaptation of the securitysystem in the new security environment has to be a reflection and result ofthe evident general overall inclusion of all the subjects, which are authorized for enforcingthe security policy.
Keywords: SWITZERLAND; SECURITY; SECURITY POLICY; NATIONAL SECURITY; SECURITY SYSTEM